DAMPAK KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, LIKUIDITAS, PROFITABILITAS, DAN KEBIJAKAN UTANG TERHADAP KEBIJAKAN DIVIDEN DI INDUSTRI PERTAMBANGAN INDONESIA - Lajar, Stephanie Natalia Ingi; Marsudi, Almatius Setya (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2021)
This study tries to see the effect of managerial ownership, institutional ownership, liquidity, profitability, and debt policy on dividend policy. Managerial ownership is measured by the ratio of the number of shares owned to total shares; institutional ownership is measured by the percentage of share ownership in the ownership structure, the current ratio is measured by dividing assets and current liabilities, debt policy is measured by dividing total debt by total equity, profitability is measured by dividing net income with total assets. Profitability is calculated by dividing net income by total assets. This study uses purposive sampling by taking data from 20 mining companies on the Indonesia Stock Exchange from 2011-2019. The technique of testing the hypothesis with multiple regression. This study proves that institutional ownership and debt policy affect the company's dividend policy. Meanwhile, managerial ownership, liquidity, and profitability do not affect dividend policy.